Kepuasan Nasabah Ditinjau Dari Kualitas Pelayanan Inti Dan Kualitas Pelayanan Periferal - Alan Rusdiana; Pipih Sopiyan; Masduki Masduki (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
Today's intense competition among banks encourages each bank to pay attention to customer needs, wants, and demands, which can be used as a marketing strategy to increase customer satisfaction. This research aims to examine the influence of core service quality and peripheral service quality on customer satisfaction. The population in this research is all 1,082 Bank BNI Persero Cikijing customers. The sample in this research was 100 customers taken using the accidental sampling technique. The data analysis method used is multiple linear regression analysis using SPSS version 21 software. The results of this research show that core service quality and peripheral service quality have a positive effect on customer satisfaction. However, in this case, the quality of core services is the dominant factor in influencing customer satisfaction.